Using the substitution u = ln(x), find the general solution of the differential equation y = x^2*(d^2(y)/dx^2) + x(dy/dx) + y = 0

dy/dx = (dy/du)(1/x), d^2(y)/dx^2 = (d^2(y)/du^2)(1/(x^2)) - (dy/du)*(1/(x^2))   

(x^2)( (d^2(y)/du^2)(1/(x^2)) - (dy/du)(1/(x^2)) ) + x(dy/du)*(1/x) + y = 0       

d^2(y)/du^2 - dy/du + dy/du + y = 0  

d^2(y)/du^2 + y = 0

y = Asin(u) + Bcos(u)

y = Asin(ln(x)) + Bcos(ln(x))                   

Related Further Mathematics A Level answers

All answers ▸

Find the integral of f(x)= x^3 + 2x^2 + 1


Could you explain to me how proof by induction works?


The plane Π contains the points (1, 2, 3), (0, 1, 2) and (2, 3, 0). What is the vector equation of the plane? and what is the cartesian equation of the plane?


Prove that (AB)^-1 = B^-1 A^-1


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences